2010
DOI: 10.1021/jp103012t
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison in Dehydrogenation Properties and Mechanism between MgCl2(NH3)/LiBH4 and MgCl2(NH3)/NaBH4 Systems

Abstract: The dehydrogenation properties and mechanism of MgCl 2 (NH 3 )/MBH 4 (here, M is Li or Na) were investigated by thermogravimetric analysis and mass spectrometry, X-ray diffraction (XRD), solid-state 11 B NMR, Fourier transform infrared, and differential scanning calorimetry (DSC). As for the MgCl 2 (NH 3 )/LiBH 4 system, it was found that a new phase, namely, MgCl 2 (NH 3 ) • LiBH 4 , to which the following dehydrogenation relates, is formed after ball milling. Judging from the reaction products, it is confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…See Figure S2 for a reference spectrum of unsolvated Mg(BH 4 ) 2. The downfield shift of the THF solvated BH4 − complex is comparable to the downfield shift reported for Mg(BH4)2·4NH3 [37]. Upon heating the two peaks collapse into a single narrow peak at 90 °C.…”
Section: Discussionsupporting
confidence: 78%
“…See Figure S2 for a reference spectrum of unsolvated Mg(BH 4 ) 2. The downfield shift of the THF solvated BH4 − complex is comparable to the downfield shift reported for Mg(BH4)2·4NH3 [37]. Upon heating the two peaks collapse into a single narrow peak at 90 °C.…”
Section: Discussionsupporting
confidence: 78%
“…À groups have a number of favorable attributes including a high hydrogen capacity, 17.6 wt% for NH 3 and 26.7 wt% for BH 4 À ; and highly mobile H d+ /H dÀ atoms which may lead to a rapid generation of H 2 and subsequent desorption at low temperature. 26,27 However, despite their promising characteristics, it has been observed that across a range of AMBs they display a variety of different thermal decomposition properties. LiBH 4 $NH 3 and Ca(BH 4 ) 2 $2NH 3 mainly release ammonia rather than hydrogen during decomposition in argon, which is attributed to the weak coordination between Li + (Ca 2+ ) with NH 3 in the material.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, except for the similar tridentate 11 B NMR spectra that are possibly related to the single or two overlapping quadrupolar resonances of BN 3 , BN 2 H or even a mixture of both, an additional peak at approximately À35 ppm was obtained for the MgCl 2 -doped sample aer heating, which can be most likely assigned to the unknown phase, as shown in Fig. 3a, i.e., the complex of MgCl 2 with AB aer heating at 130 C. 25,26 Third, we further employed in situ Raman spectroscopy to examine the entire process of thermal decomposition. Fig.…”
mentioning
confidence: 79%